2011
DOI: 10.1111/j.1445-2197.2011.05779.x
|View full text |Cite
|
Sign up to set email alerts
|

How can we build mentorship in surgeons of the future?

Abstract: Formalizing the mentoring process, with local, national and international schemes, will initiate mentoring relationships and cultivate a mentoring culture. Ultimately, this will maintain and improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…They identified being a role model, having surgical expertise, and professional integrity as important aspects of being a mentor. Other attributes include being a supporter, emotionally intelligent, and intellectually honest (13). Another study (5) surveyed K award recipients , in which respondents reported that mentors could be advocates, provide networking, and grant writing skills.…”
Section: Attributes Of a Good Mentor And Of A Good Menteementioning
confidence: 99%
See 1 more Smart Citation
“…They identified being a role model, having surgical expertise, and professional integrity as important aspects of being a mentor. Other attributes include being a supporter, emotionally intelligent, and intellectually honest (13). Another study (5) surveyed K award recipients , in which respondents reported that mentors could be advocates, provide networking, and grant writing skills.…”
Section: Attributes Of a Good Mentor And Of A Good Menteementioning
confidence: 99%
“…Mentorship in general has been explored, as well as gender specific differences or issues that arise. The literature is comprised largely of surveys (1)(2)(3)(4)(5)(6)(7)(8), commentaries (9-12), reviews (13)(14)(15)(16), and interviews (17). Very few studies show causality, or active intervention and outcomes of mentorship programs (8,18,19).…”
Section: Contextmentioning
confidence: 99%
“…Surgery: Three surgical reviews described use of formal mentoring approaches [17,27,32]. Healy et al reported that residents preferred formal mentoring approaches given its structured approach, the availability of trained mentors and the presence of clear mentoring objectives [17].…”
Section: Formal Mentoring Approachmentioning
confidence: 99%
“…Formal mentoring sees mentors assigned to mentees [26] in a process initiated and assisted by the host organization to facilitate access to mentors and increase the number of mentoring relationships [32].…”
Section: Formal Versus Informal Mentoringmentioning
confidence: 99%
See 1 more Smart Citation